2008
DOI: 10.3174/ajnr.a0850
|View full text |Cite
|
Sign up to set email alerts
|

Altered Diffusion in the Frontal Lobe in Parkinson Disease

Abstract: BACKGROUND AND PURPOSE:Parkinson disease (PD) is characterized by basal ganglia abnormalities. However, there are neurodegenerative changes in PD that extend beyond the basal ganglia and that are not sufficiently evaluated with standard MR imaging. The aim of this study was to characterize whole-brain gray matter (GM) and white matter (WM) changes in PD by using diffusion tensor imaging (DTI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
88
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(101 citation statements)
references
References 37 publications
11
88
0
Order By: Relevance
“…Both identified anatomical networks are strikingly similar to regions reported in previous studies in PD and healthy controls as being functionally connected to the posterior putamen (Helmich et al, 2010; Tziortzi et al, 2014). The prefrontal regions identified in our study are also consistent with regions showing diffusion alterations in PD patients (Kendi et al, 2008). The anatomical networks are also consistent with recent findings reporting these regions to be associated with altered activity and connectivity in PD patients during execution and attention to novel versus automatic movements (Wu et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…Both identified anatomical networks are strikingly similar to regions reported in previous studies in PD and healthy controls as being functionally connected to the posterior putamen (Helmich et al, 2010; Tziortzi et al, 2014). The prefrontal regions identified in our study are also consistent with regions showing diffusion alterations in PD patients (Kendi et al, 2008). The anatomical networks are also consistent with recent findings reporting these regions to be associated with altered activity and connectivity in PD patients during execution and attention to novel versus automatic movements (Wu et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…Two recent meta-analyses (Shao et al 2015; Yu et al 2015) investigated volume changes in patients with PD compared to controls using a plethora of studies (Burton et al 2004; Cordato et al 2005; Nagano-Saito et al 2005; Summerfield et al 2005; Beyer et al 2007; Ramirez-Ruiz et al 2007; Karagulle Kendi et al 2008; Camicioli et al 2009; Jubault et al 2009; Martin et al 2009; Pereira et al 2009; Sanchez-Castaneda et al 2009; Tir et al 2009; Dalaker et al 2010; Kostic et al 2010; Nishio et al 2010; Cerasa et al 2011; Focke et al 2011a, b; Meppelink et al 2011; Compta et al 2012; Fernandez-Seara et al 2012; Hong et al 2012; Ibarretxe-Bilbao et al 2012; Tessitore et al 2012a ; Lee et al 2013a; O’Callaghan et al 2013; Ellfolk et al 2014; Menke et al 2014; Sehm et al 2014) using VBM. Reduced GM volume was noted in the frontal lobe including bilateral middle and inferior frontal gyri and the left precentral gyrus, the parietal lobe including the left superior parietal lobule and precuneus, the occipital lobe including bilateral cuneus, and the limbic lobe including the left anterior cingulate in one meta-analysis (Shao et al 2015).…”
Section: Diagnosis Of Pdmentioning
confidence: 99%
“…49 Another study found decreased fractional anisotropy in the frontal lobes in PD patients without cognitive impairment and with no evidence of brain volume loss. 50 …”
Section: Imaging White Matter Lesionsmentioning
confidence: 99%